Peran Agama dalam Negara Menurut Ibnu Khaldun - Davit Hardiansyah Putra (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2022)
Abstract: The formulation of the problem of this research is how the role of religion in the country according to Ibn Khaldun. This type of research is library research and the method used in this research is descriptive qualitative. This study shows that Ibn Khaldun divided the role of religion into three types, namely: 1. Religion as a unifier, religion became an important role in social and political life, namely the unifying factor and community solider. If religion coexists with solidarity then it will contribute in realizing the integrity of political power.2. Religion as a driver of success, the state and power can stand without religion, but it is religion that brings the state and power towards a better direction. 3. Religion as the legitimacy of the political system, religion is used as a legal basis that must be obeyed in carrying out politics or government. According to Ibn Khaldun, a government based on religion is more important because he thinks that this kind of government is the best. Without religion group unity is only based on a sense of natural unity (Ashabiyah) that is formed due to the similarity of tribes or family relations. The nature of this natural unity is relatively fragile and a religious foundation is needed as a basis for the group's sense. This is mainly because religion is able to guarantee group morality, virtue, distance individual malignancies and be able to become an adhesive tool for identity that keeps them away from social conflict. Keyword: Government, Ibn Khaldun, Religion, and Country.